Composing through Interaction: a framework for collaborative music composition based on human interaction on public spaces - Amazonas, Mauro; Castro, Thais; de Freitas, Rosiane; Gadelha, Bruno (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação Musical, 2019)
Urban public art is a kind of art that is produced and demonstrated in public places, based on the function and connotation of the city itself exerts. As an essential artistic content in the contact of human life, the introduction of technology is a significant trend in public art, and with it, the interaction has become an increasingly relevant aspect of public art in the digital context. In this way, this work presents an environment for creating random collaborative music from interaction in public spaces using mobile technology. The result is a composition that goes towards to John Cage’s methods. However, in our case, all participants are composers and their interactions with space work as the component that brings randomness to composition. A case study was conducted with volunteer students divided into groups. Participants made use of two versions of Compomus - an app developed for immersive interaction with sound. One version encourages movement through the environment, while the other explores the spatiality of sound in a simulated public environment within the university. The interaction of the participants generated ten compositions, five from the first version and five compositions from the second version of the developed application. The sounds resulting from the interaction were made available to the public through a website.